TRANSFORMASI BUDAYA MESEURAYA PASCA PENANGGULANGAN BENCANA TSUNAMI 2004 DI GAMPONG KEUB KABUPATEN ACEH BARAT - Triyanto Triyanto; Nellis Mardhiah (Jurnal Community, 2020)
Indonesia as a country that is considered to have a wealth of disasters requires everyone to understand the potential for disasters in their respective regions. Not just understanding but also knowing how to deal with and even tame. The tsunami in Aceh which shocked the world forced international institutions to play an active role in disaster management. But mistakes in disaster management can have fatal consequences because in general disaster management is also accompanied by the restoration of social and cultural values there is a shift in social values in society. In this article, it is revealed how the Keub Gampoeng community performs the survey and reveals how disaster management can cause changes in the values of society. The study was conducted qualitatively with in-depth interviews and observation data collection techniques. The results showed that the community since before the tsunami had been accustomed to doing meseuraya, namely cleaning the surrounding environment, mosques, and also the community as individuals, especially those who were carrying out khanduri or carrying out celebrations such as marriage, circumcision, or showering (birth procession). Meanwhile, the handling of natural disasters by several non-government organizations (NGOs) can also result in changes in attitudes towards business activities. Especially handling disasters that are considered inappropriate. It can be exemplified is the implementation of cash for a work program that is echoed as cooperation paid. The research data shows that the community is eventually accustomed to doing the payment for payment so that when village officials conduct the meeting without payment, the community is no longer eager to implement the meeting.